Central cervical fibroid mimicking as chronic uterine inversion: a case report - Singh, Swati; Chaudhary, Priyakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Leiomyomas are most common benign gynaecological tumor. Most of the fibroids are situated in the body of the uterus, but only in 1-2% cases, they are confined to cervix.We report a case of 33 years old women, para 2 live 2 diagnosed as myomatous polyp on ultrasound and clinically as chronic inversion of uterus. On surgery, we found it as central cervical fibroid with uterus sitting on the fibroid i.e. lantern on the St. Paul’s.